Performance appraisal satisfaction: the role of feedback and goal orientation - Culbertson, Satoris S.; Henning, Jaime B.; Payne, Stephanie C. (My University, 2013)
Employee satisfaction with performance appraisal (PA) plays a large role in the perceived effectiveness of PA. We examined the joint effects of feedback sign (positive or negative) and three goal orientation dimensions (learning, performance-prove, performance-avoid) on PA satisfaction. Results revealed the negative relationship between negative feedback and PA satisfaction was stronger for those higher in performance-prove (PPGO), performance-avoid, and learning goal orientation. Additionally, the relationship between positive feedback and PA satisfaction was stronger for individuals low on PPGO and weaker for individuals high on PPGO. Implications for enhancing PA reactions are discussed.
Keywords: Performance appraisal; Goal orientation; Feedback sign; Satisfaction